Marriage Risk Avoidance and Resource Transformation among Rural Women with Disabilities - Xu, Lihua; Tian, Xiaoming; Hu, Xiongbang (New Countryside, 2026)
This study investigates the marital choices of rural women with disabilities within a town located in Northwest China, a population positioned at the intersection of gender, disability, and rural disadvantage. Grounded in Bourdieu’s theoretical insights on capital, the study theorizes marriage as a strategic social field in which vulnerable women assess risks, mobilize resources, and convert different forms of capital under conditions of structural inequality. The study draws on qualitative interviews with rural women with disabilities and employs thematic analysis to examine their marital trajectories, survival risks, and negotiation practices within this specific context. The analysis focuses on experiences involving alcoholic or violent spouses, limited social support due to geographic proximity, housing location, employment stability, and household authority structures. Findings show that in this study, participants actively avoid high-risk partners and prioritize spouses with stable incomes and urban housing to enhance safety and social support. When options are limited, they make constrained choices to accept older spouses or those with caregiving responsibilities or disabilities in exchange for economic security or personal autonomy. These are not fully autonomous decisions but survival-oriented trade-offs under structural constraints. These practices reflect survival-oriented rationality rather than passivity, revealing the capital flow mechanisms of marginalized women in unequal marriage markets and underscoring the need for multi-level policy interventions to support their social integration and sustainable capital accumulation, while highlighting that their direct applicability to broader populations requires further research.